Etika Administrasi Dalam Layanan Publik Yang Mengutamakan Keadilan Sosial - Musri; Sayid Anshar; Netrivianti; Adi Wibowo (Ekasakti Jurnal Penelitian dan Pengabdian)
This research aims to explore the role of ethics in public administration and how its application can contribute to social justice. In this case, administrative ethics includes moral norms that must be upheld by the State Civil Apparatus (ASN) when providing services to the community. The method used in this study is a quantitative approach involving ASNs as respondents from various government agencies. Data collection was conducted through a survey that examined variables such as personal values, motivation, religious beliefs, working conditions, organizational culture, and social pressure. The analysis was conducted to identify how these factors influence the practice of social piety among ASNs and its impact on the effectiveness of public services and public trust in the bureaucracy.Results: Findings show that social piety has a significant effect on the quality of public services. ASNs who have high ethical awareness tend to provide better and fairer services to the community. This study also revealed that support from a positive work environment and organizational culture can improve ethical practices in public administration.Implications: The findings of this study are expected to provide deeper insights into the importance of ethical practices in public administration and assist in the formulation of policies that support integrity and improve the quality of public services in the future.